The Effect of Social Media Marketing and Customer Experience on Customer Satisfaction in Furniture Stores in Bitung City with the Mediating Role of Disconfirmation - Makoli, Felisya Feriska Syalomita; Indrajit, Indrajit (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study was conducted due to the increasing competition between furniture stores and suppliers in Bitung City, where many suppliers sell directly through social media at lower prices, potentially reducing customer satisfaction for furniture stores. The purpose of this research is to analyze the influence of Social Media Marketing and Customer Experience on Customer Satisfaction, as well as to examine whether Disconfirmation serves as a mediating variable. A quantitative approach was applied using a survey design, with data collected through questionnaires from 157 respondents and analyzed using PLS-SEM. The findings show that Social Media Marketing and Customer Experience have a positive and significant effect on Customer Satisfaction. Both variables also significantly influence Disconfirmation, and Disconfirmation is proven to mediate these relationships. These results indicate that customer satisfaction increases when marketing information and shopping experiences meet expectations, implying that businesses should maintain consistent information and enhance service quality.